Short-term effects of olive-mill-wastes-derived biochars amendment and arbuscular mycorrhizal fungi inoculation on growth of maize (Zea mays) and mycorrhizal colonization - Minkosse, Christiane; Langenfeld, Aude; Azzaz, Ahmed Amine; Jeguirim, Mejdi; El-Bassi, Leila; Akrout, Hanene; Jellali, Salah; Ghimbeu, Camélia Matei; Nassr, Najat (Comptes Rendus. Chimie, 2023)
The viability of arbuscular mycorrhizal fungi (AMF) spores formulated with biochars derived from the pyrolysis of raw (ROP) or impregnated olive pomace with olive mill wastewaters (IROP) was investigated under laboratory-controlled conditions. A greenhouse experiment was also conducted to study the effect of AMF spores and biochars adding on the growth of maize plants. Nine treatments, combining one biochar (ROP or IROP) at a level of 2.5 g/kg of soil and inoculation or not with Funneliformis mosseae at two concentrations (30 and 125 spores/kg of soil), were arranged in an entirely randomized block design. The results of the formulation trial showed that arbuscular mycorrhizal fungi (AMF) spores had short-term viability and are sensitive to the presence of biochar. This effect is more pronounced when the biochar is made from IROP. Both the AMF and biochars treatments did not significantly enhance the growth of maize plants, biomass production, and leaf chlorophyll contents. However, the most significant effect on nutrients uptake was observed in the modalities treated with AMF alone (30 spores/kg of soil) and AMF combined with the biochar made from IROP (IROP $+$ 30 spores/kg of soil). In those modalities, the N uptake was improved by 45% and 33%, respectively. Moreover, biochar addition to the soil did not particularly enhance root colonization by AMF and no negative effect of its application was observed either. However, the inoculation of spores enhanced propagules production and maize root colonization.